PERENCANAAN DISTRIBUSI PRODUK GAS PT.REBBAK TROLIH LESTARI MENGGUNAKAN METODE DISTRIBUTION REQUIREMENT PLANNING (DRP) - Maya Asyifa Aulia; Lintang Sari Fajhriana; Faizal Aziz; Mochammad Fauzi (Jurnal Bayesian : Jurnal Ilmiah Statistika dan Ekonometrika, 2022)
PT. Rebbak Trolih Lestari is a company engaged in Elpiji Gas Distribution from PT. Pertamina Indonesia. The company has one warehouse hoarding elpiji gas cylinders and has a problem of lack of supplies that cause unmet demand. PT. Rebbak Trolih Lestari does not have good distribution planning. With this problem, research was conducted using the Distribution Requirement Planning (DRP) method. Distribution Requirement Planning (DRP) is a method of handling procurement in a distribution network. The purpose of this study is to distribute good activities so that success in meeting customer demand will be more optimal, improved sales performance in fulfilling orders on time and the right amount of inventory